THE IMPACT OF THE WAR ON THE DEVELOPMENT OF THE GRAIN MARKET IN UKRAINE (INNOVATIVE ECONOMY, 2024)
Bodnar O.V. THE IMPACT OF THE WAR ON THE DEVELOPMENT OF THE GRAIN MARKET IN UKRAINEPurpose. The aim of the article is to study the development of the grain market in Ukraine in the conditions of military aggression of the russian federation, price volatility of domestic and foreign markets, assessment of the consequences of an armed attack on the production and formation of internal and external conditions of grain supply.Methodology of research. The author used a number of general scientific and special methods and approaches. In particular, the abstract and logical, analytical and monographic methods was used to highlighted the conditions of functioning of the grain market in Ukraine during the war, the comparative analysis was used to research in the pre-war and war periods  of its development; statistical method helped the author to process on supply and demand data, price situation on the grain market, revealed the impact of the consequences of the armed conflict on the grain market; the method of cause-and-effect analysis helped to investigate the price trends of the domestic and global wheat market; correlation-regression analysis revealed the impact of the war on futures fluctuations on the European stock market; the method of logical generalization used to make a forecast of the grain market in 2023/24 MY.Findings. The conditions of functioning of grain in Ukraine during the war were comprehensively considered, which made it possible to reveal the consequences of the armed conflict on its condition. The peculiarities of the price volatility of the domestic and world wheat market were investigated. The impact of the war on the change in the relationship between the prices of the domestic market of Ukraine and the world market was revealed. The forecast of the grain market in 2023/24 MY, was offered.Originality. The forecast balances of grain during the war period were refined. The study of price volatility of grain in crisis conditions had gained further development. The market changes of the relationships between the price of the domestic and world markets in the limited opportunities for exporting domestic food were evaluated.Practical value. The results of the research can be used in the work of state executive bodies. In particular, the forecast for the development of the grain market in 2023/24 MY can be helpful to make comprehensive forecasts for the development of the agricultural sector. The directions for agrarian policy in terms of the development of the grain products thereof export can be used in the development state decisions regarding priority directions to increase the export potential of the grain industry as well as to introduce European cooperation projects in the agrarian sphere. Key words: grain market of Ukraine, war in Ukraine, world grain market, supply, demand, price, market situation, wheat, corn, barley, export, import, grain market balance, grain producers, grain exporters.
Keywords: grain market of Ukraine; war in Ukraine; world grain market; supply; demand; price; market situation; wheat; corn; barley; export; import; grain market balance; grain producers; grain exporters.